Analises das diferencas em rendimento da mandioca entre estacoes experimentais e os campos de agricultores - Correa, H. (International Center for Tropical Agriculture, 1991)
The different factors that affect yield stability over time are discussed on the basis of results of numerous studies carried out at the exptl. station and on-farm levels. Among these are soil and climatic conditions, pests and diseases, use of different cultural practices (planting, spacing, cropping sytem, harvest time, double vs. single rows), plot size, and socioeconomic level of the farmer. Results of comparative yield trials using recommended vs. traditional cultural practices are also discussed. (CIAT)